High-entropy alloy with room-temperature and high-temperature toughness as well as preparation method and application of high-entropy alloy

By precisely controlling the element ratio and alloy structure of high-entropy alloys, combined with two-step aging treatment process, the problem of insufficient mechanical properties of existing high-entropy alloys at room temperature and high temperature is solved, and the strength and toughness improvement in the medium temperature range is achieved and Excellent performance of mechanical properties.

CN119464879APending Publication Date: 2025-02-18THE HONG KONG POLYTECHNIC UNIV SHENZHEN RES INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411470696.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing high entropy alloy materials cannot have good mechanical properties at room temperature and high temperatures, especially in the medium temperature range, limiting their use in engineering applications.

Method used

By precisely controlling the elemental ratio of Al, Co, Cr, Fe, Ti, Ta, B and Ni, a high-entropy alloy with room temperature and high temperature strength and toughness was designed. The alloy structure includes FCC matrix and L12 nanometer precipitation in its alloy structure. and optimize the mechanical properties of the alloy through a two-step aging process.

Benefits of technology

It has achieved excellent mechanical properties at room temperature and high temperatures, including the improvement of yield strength, tensile strength and elongation, and is suitable for aerospace, petrochemical and power equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464879A_ABST
    Figure CN119464879A_ABST
Patent Text Reader

Abstract

The invention relates to the field of high-entropy alloys, in particular to a high-entropy alloy with room-temperature and high-temperature obdurability as well as a preparation method and application of the high-entropy alloy. The high-entropy alloy with room-temperature and high-temperature obdurability comprises the following chemical components in percentage by atom: 4.0 to 6.0 percent of Al, 15.0 to 20.0 percent of Co, 20.0 to 25.0 percent of Cr, 15.0 to 20.0 percent of Fe, 4.0 to 6.0 percent of Ti, 0.5 to 2.0 percent of Ta, 0.1 to 0.5 percent of B and the balance of Ni, and satisfies 10.0% < = (Ti + Al + Ta) < = 12.0% and (Cr + Fe) < = 40.0%. The high-entropy alloy with room-temperature and high-temperature toughness shows good room-temperature and high-temperature mechanical properties, has good yield strength, tensile strength and ductility in both room-temperature and high-temperature environments, and can be well applied to the fields of aerospace, petrochemical engineering, electrical equipment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of high entropy alloys, and in particular to a high entropy alloy having both room temperature and high temperature toughness, and a preparation method and application thereof. Background Art

[0002] The development of metal structural materials with excellent high-temperature mechanical properties is crucial for the development of aerospace, petrochemical and power equipment. In recent years, studies have found that multi-component high-entropy alloys have opened up new avenues for material development and performance improvement with their unique microstructures and mechanical properties. Among them, FCC (face-centered cubic) high-entropy alloys strengthened by L12 nano-precipitates have attracted much attention. The microstructures of these alloys are similar to commercial nickel-based and cobalt-nickel-based high-temperature alloys strengthened by γ' precipitation phases, so they are expected to become candidate materials for applications in high-temperature environments.

[0003] In order to make the FCC high entropy alloy strengthened by L12 nano-precipitation phase have good high temperature mechanical properties, researchers have carried out a lot of work. However, the high temperature strength of this type of alloy is still low, and most of the alloys also show the characteristics of medium temperature brittleness (400-800℃), which greatly limits its application in engineering. For example, the room temperature yield strength of Inconel 718 nickel-based high temperature alloy is 1030MPa, while the yield strength at 800℃ is only 600MPa; the Al2O3 alloy developed by Tsai et al. 0.5 The tensile yield strength of CoCrCuFeNi alloy drops rapidly from 600MPa at 400℃ to 60MPa at 800℃. At the same time, the alloy also exhibits severe medium-temperature brittleness between 400 and 700℃. In addition, the (CoCrFeNi) 94 The yield strength of Al4Ti2 high entropy alloy at 800℃ is only 100MPa; the (Ni2Co2FeCr) designed by Zhao et al. 92 The yield strength of Al4Nb4 alloy at 760°C reaches 720MPa, but the elongation is only 5%. It can be seen that the existing high entropy alloy materials still cannot have good mechanical properties at both room temperature and high temperature.

[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a high entropy alloy having both room temperature and high temperature toughness and a preparation method and application thereof, aiming to solve the problem that existing high entropy alloy materials cannot have good mechanical properties at both room temperature and high temperature.

[0006] The technical solution of the present invention is as follows:

[0007] A first aspect of the present invention provides a high entropy alloy having both room temperature and high temperature toughness, wherein the chemical composition of the high entropy alloy includes, in atomic percentage, 4.0-6.0% Al, 15.0-20.0% Co, 20.0-25.0% Cr, 15.0-20.0% Fe, 4.0-6.0% Ti, 0.5-2.0% Ta, 0.1-0.5% B, and the rest Ni; and satisfies 10.0%≤(Ti+Al+Ta)≤12.0%, (Cr+Fe)≤40.0%.

[0008] Optionally, the chemical composition of the high entropy alloy includes, in atomic percentage, 4.0-6.0% Al, 16.5-18.5% Co, 20.5-23.5% Cr, 16.5-18.5% Fe, 4.0-6.0% Ti, 1.5-2.0% Ta, 0.1-0.4% B, and the rest Ni; and satisfies 10.0%≤(Ti+Al+Ta)≤12.0%, (Cr+Fe)≤40.0%.

[0009] Optionally, the alloy structure of the high entropy alloy includes an FCC matrix and an L12 nano-precipitation phase.

[0010] Optionally, in the alloy structure of the high entropy alloy, the volume fraction of the L12 nano-precipitation phase is greater than or equal to 35%.

[0011] Optionally, the L12 nano-precipitated phase has a first size and a second size, the first size is 40-100 nm, and the second size is 1-20 nm.

[0012] Optionally, at room temperature, the yield strength of the high entropy alloy is greater than or equal to 1100 MPa, the tensile strength is greater than or equal to 1500 MPa, and the elongation is greater than or equal to 15%; at a temperature of 800°C, the yield strength of the high entropy alloy is greater than or equal to 900 MPa, the tensile strength is greater than or equal to 1000 MPa, and the elongation is greater than or equal to 8%.

[0013] The second aspect of the present invention provides a method for preparing the high entropy alloy having both room temperature and high temperature toughness according to the present invention, which comprises the steps of:

[0014] The raw materials Al, Co, Cr, Fe, Ti, Ta, B and Ni are mixed and smelted in proportion, cast into alloy ingots after smelting, and cooled to room temperature;

[0015] The obtained alloy ingot is homogenized at 1100-1200°C for 1-2 hours and then cooled to room temperature;

[0016] The alloy ingot which has been homogenized is rolled at a reduction of 5 to 10% each time to obtain a plate with a total reduction of 60 to 80%;

[0017] The obtained plate is subjected to recrystallization treatment at 1150-1200°C for 2-5 minutes and then cooled to room temperature;

[0018] The recrystallized plate is subjected to a two-step aging treatment. The first step of aging treatment is carried out at 980-1050°C for 10-30 minutes, and then cooled to room temperature. The second step of aging treatment is continued at 780-850°C for 1-24 hours, and then cooled to room temperature to obtain a high-entropy alloy with both room temperature and high temperature strength and toughness.

[0019] Optionally, the purity of the raw materials Al, Co, Cr, Fe, Ti, Ta, B and Ni is greater than or equal to 99.95%.

[0020] Optionally, the mixed smelting process is: placing the raw materials Al, Co, Cr, Fe, Ti, Ta, B and Ni in a smelting furnace in proportion, and smelting them multiple times under electromagnetic stirring.

[0021] The third aspect of the present invention provides an application of the high entropy alloy having both room temperature and high temperature toughness in the fields of aerospace, petrochemical or power equipment.

[0022] Beneficial effects: The present invention provides a high entropy alloy with both room temperature and high temperature toughness, which exhibits good room temperature and high temperature mechanical properties, and has good yield strength, tensile strength and elongation under both room temperature and high temperature environments. In addition, the present invention accurately controls the element ratio of Al, Co, Cr, Fe, Ti, Ta, B and Ni, adopts a mixed smelting method to prepare an alloy ingot, and then obtains a high entropy alloy with both room temperature and high temperature toughness through homogenization treatment, rolling treatment, recrystallization treatment and two-step aging treatment. The preparation method is simple to operate, has strong process controllability, and is easy to realize industrial production. The high entropy alloy with both room temperature and high temperature toughness provided by the present invention can be applied to aerospace, petrochemical, power equipment and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the equilibrium phase diagram of the high entropy alloy in Example 1 calculated using Thermal-calc software.

[0024] Figure 2 This is a scanning electron microscope image of the alloy structure of the high entropy alloy in Example 1.

[0025] Figure 3This is a scanning electron microscope image of the alloy structure of the high entropy alloy in Comparative Example 1.

[0026] Figure 4 This is a scanning electron microscope image of the alloy structure of the high entropy alloy in Comparative Example 2.

[0027] Figure 5 The high entropy alloy prepared in Example 1, Al 10 Co 25 Cr8Fe 15 Ni 36 Ti6, Co-9Al-9W-2Ta-2Mo, Inconel 718, Inconel 625 and AlCoCrFeNi 2.1 The relationship between yield strength and temperature. DETAILED DESCRIPTION

[0028] The present invention provides a high entropy alloy having both room temperature and high temperature toughness and a preparation method and application thereof. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0029] The present invention is based on the design concept of high entropy alloy. By accurately controlling the element ratio of Al, Co, Cr, Fe, Ti, Ta, B and Ni, the volume fraction of L12 nano-precipitate phase reaches more than 35%. At the same time, according to the thermodynamic calculation results, a two-step aging heat treatment method is adopted to ensure that the alloy structure is only FCC matrix and L12 nano-precipitate phase. The high entropy alloy finally developed has good mechanical properties both at room temperature and high temperature.

[0030] Based on the above design concept, an embodiment of the present invention provides a high entropy alloy with both room temperature and high temperature toughness, wherein, in terms of atomic percentage, the chemical composition of the high entropy alloy includes: Al is 4.0-6.0% (for example, it can be 4.0%, 4.5%, 5.0%, 5.5%, 6.0%), Co is 15.0-20.0% (for example, it can be 15.0%, 15.5%, 16.0%, 16.5%, 17.0%, 17.5%, 18.0%, 18.5%, 19.0%, 19.5%, 20.0%), Cr is 20.0-25.0% (for example, it can be 20.0%, 20.5%, 21.0%, 21.5%, 22.0%, 22.5%, 23.0%, 23.5%, 24.0%, 24.5%). 5%, 25.0%), Fe is 15.0-20.0% (for example, it can be 15.0%, 15.5%, 16.0%, 16.5%, 17.0%, 17.5%, 18.0%, 18.5%, 19.0%, 19.5%, 20.0%), Ti is 4.0-6.0% (for example, it can be 4.0%, 4.5%, 5.0%, 5.5%, 6.0%), Ta is 0.5-2.0% (for example, it can be 0.5%, 1.0%, 1.5%, 2.0%), B is 0.1-0.5% (for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%), and the rest is Ni; and 10.0%≤(Ti+Al+Ta)≤12.0%, (Cr+Fe)≤40.0% is satisfied.

[0031] This embodiment provides a high entropy alloy with both room temperature and high temperature toughness. By precisely controlling the element ratios of Al, Co, Cr, Fe, Ti, Ta, B and Ni, a high entropy alloy with excellent mechanical properties at both room temperature and high temperature environments is obtained. The high entropy alloy provided in this embodiment is an Al-Co-Cr-Fe-Ni-Ti-Ta-B series high entropy alloy, and its chemical composition design is based on the following:

[0032] The Al-Co-Cr-Fe-Ni-Ti-Ta-B series high entropy alloy uses Ni, Co, Cr and Fe as matrix phase elements. The atomic radius difference between these four elements is small, which can ensure a large solid solubility and form a typical FCC (face-centered cubic) single-phase structure.

[0033] Ni and Co are important basic elements of the high entropy alloy of the present invention. They are not only constituent elements of the FCC matrix phase, but also important forming elements of the multi-component L12 nano-precipitation phase. And Ni and Co are both high temperature resistant elements, which are beneficial to improving the high temperature resistance of the alloy. In the high entropy alloy of the present invention, the content of Co is controlled to be 15.0-20.0%, and the content of Ni is controlled to be the remainder after removing the contents of the other seven elements.

[0034] Cr is one of the important anti-oxidation alloying elements in the high entropy alloy of the present invention. The alloy should have enough Cr to achieve good high-temperature anti-oxidation performance, but the addition of Cr will induce the precipitation of σ phase at the grain boundary, causing brittle fracture of the alloy. Therefore, it is necessary to accurately control the Cr content and heat treatment process, so as to control the content of σ phase in the alloy structure to be less than 5% to ensure the strength of the alloy. In the high entropy alloy of the present invention, the Cr content is controlled to be 20.0-25.0%.

[0035] Fe is a forming element of the FCC matrix phase and can be used to replace part of Ni and Co to reduce the cost of the alloy. However, excessive Fe is likely to reduce the oxidation resistance of the alloy and will precipitate with Cr to produce σ phase, causing brittle fracture of the alloy. In the high entropy alloy of the present invention, the Fe content is controlled to be 15.0-20.0%.

[0036] Al, Ti and Ta are all important forming elements of multi-component L12 nano-precipitated phase, wherein the addition of Ti and Ta can improve the strengthening effect of L12 precipitated phase, and by optimizing the content and proportion of Al, Ti and Ta elements, the volume fraction, size, morphology and intrinsic physical properties of L12 nano-precipitated phase can be effectively controlled, thereby obtaining a significant strengthening effect. In the high entropy alloy of the present invention, the content of Al is controlled to be 4.0-6.0%, the content of Ti is 4.0-6.0%, the content of Ta is 0.5-2.0%, and 10.0%≤(Ti+Al+Ta)≤12.0%.

[0037] B acts as a grain boundary binder. A small amount of B element can be concentrated at the grain boundary to enhance the grain boundary bonding force and improve the alloy plasticity. In the high entropy alloy of the present invention, the content of B is controlled to be 0.1-0.5%.

[0038] In some preferred embodiments, the chemical composition of the high entropy alloy includes, in atomic percentage, 4.0-6.0% Al, 16.5-18.5% Co, 20.5-23.5% Cr, 16.5-18.5% Fe, 4.0-6.0% Ti, 1.5-2.0% Ta, 0.1-0.4% B, and the rest Ni; and satisfies 10.0%≤(Ti+Al+Ta)≤12.0%, (Cr+Fe)≤40.0%.

[0039] In some embodiments, the alloy structure of the high entropy alloy includes an FCC matrix and an L12 nano-precipitation phase.

[0040] The FCC matrix in the high entropy alloy structure of the present invention has good deformation ability, which is the key to the alloy obtaining good plasticity. The L12 nano-precipitated phase can effectively hinder the dislocation movement and play a role in precipitation strengthening. At the same time, the L12 nano-precipitated phase can maintain a coherent relationship with the matrix and has excellent thermal stability.

[0041] In some embodiments, in the alloy structure of the high entropy alloy, the volume fraction of the L12 nano-precipitated phase is greater than or equal to 35%. The present invention achieves a volume fraction of the L12 nano-precipitated phase of more than 35% by precisely controlling the element ratios of Al, Co, Cr, Fe, Ti, Ta, B and Ni, thereby significantly improving the precipitation strengthening effect.

[0042] In some embodiments, the L12 nano-precipitated phase has a first size and a second size, the first size is 40-100 nm, and the second size is 1-20 nm.

[0043] In this embodiment, the L12 nano-precipitated phase has a first size and a second size. The precipitated phase of the first size is formed during the first step of aging treatment, and can be formed both inside the grain and at the grain boundary. In addition to providing an effective precipitation strengthening effect, it can also inhibit the precipitation of the σ brittle phase at the grain boundary, avoiding the grain boundary brittleness problem; the precipitated phase of the second size is formed during the second step of aging treatment. At this temperature, the alloy has a greater supersaturation and precipitation driving force, which increases the volume fraction of the precipitated phase and forms a dense second-sized precipitated phase; the combined effect of the two sizes of precipitated phases can maximize the precipitation strengthening effect, while avoiding the grain boundary brittleness problem, and obtaining a good strength-plasticity match.

[0044] An embodiment of the present invention provides a high-entropy alloy with both room temperature and high temperature toughness. The high-entropy alloy has excellent room temperature and high temperature mechanical properties. At room temperature, the yield strength of the high-entropy alloy is greater than or equal to 1100 MPa, the tensile strength is greater than or equal to 1500 MPa, and the elongation is greater than or equal to 15%; at a temperature of 800°C, the yield strength of the high-entropy alloy is greater than or equal to 900 MPa, the tensile strength is greater than or equal to 1000 MPa, and the elongation is greater than or equal to 8%. The high-entropy alloy can be applied to aerospace, petrochemical, power equipment and other fields.

[0045] In some embodiments, at room temperature, the high entropy alloy has a yield strength greater than 1100 MPa, a tensile strength greater than 1500 MPa, and an elongation greater than 15%; at a temperature of 800°C, the high entropy alloy has a yield strength greater than 900 MPa, a tensile strength greater than 1000 MPa, and an elongation greater than 8%.

[0046] The present invention also provides a method for preparing a high entropy alloy having both room temperature and high temperature toughness as described in any of the above embodiments, which comprises the steps of:

[0047] The raw materials Al, Co, Cr, Fe, Ti, Ta, B and Ni are mixed and smelted in proportion, cast into alloy ingots after smelting, and cooled to room temperature;

[0048] The obtained alloy ingot is homogenized at 1100-1200°C for 1-2 hours and then cooled to room temperature;

[0049] The alloy ingot which has been homogenized is rolled at a reduction of 5 to 10% each time to obtain a plate with a total reduction of 60 to 80%;

[0050] The obtained plate is subjected to recrystallization treatment at 1150-1200°C for 2-5 minutes and then cooled to room temperature;

[0051] The recrystallized plate is subjected to a two-step aging treatment. The first step of aging treatment is carried out at 980-1050°C for 10-30 minutes, and then cooled to room temperature. The second step of aging treatment is continued at 780-850°C for 1-24 hours, and then cooled to room temperature to obtain a high-entropy alloy with both room temperature and high temperature strength and toughness.

[0052] In this embodiment, by selecting a suitable raw material ratio of Al, Co, Cr, Fe, Ti, Ta, B and Ni, the volume fraction of L12 nano-precipitated phase in the alloy structure prepared later is more than 35%, the raw material is first prepared by a mixed smelting method to obtain an alloy ingot, and then a high entropy alloy with both room temperature and high temperature toughness is obtained by homogenization, rolling, recrystallization and two-step aging treatment. The two-step aging treatment is a key step, which can ensure that the alloy structure of the high entropy alloy is only FCC matrix and L12 nano-precipitated phase, wherein the first step of aging treatment makes part of the primary L12 phase precipitate preferentially at the grain boundary, occupying the grain boundary nucleation site, reducing the grain boundary energy, inhibiting the formation of σ phase during low temperature aging, and avoiding the occurrence of medium temperature brittleness of the alloy; the second step of aging treatment promotes the precipitation of high-density secondary L12 phase, which significantly improves the strength of the alloy. The high entropy alloy obtained by the preparation method described in this embodiment exhibits good room temperature and high temperature mechanical properties, and has good yield strength, tensile strength and elongation at room temperature and high temperature environments.

[0053] In some embodiments, the purity of the raw materials Al, Co, Cr, Fe, Ti, Ta, B and Ni is greater than or equal to 99.95% to ensure the strength and toughness of the high entropy alloy prepared subsequently.

[0054] In some embodiments, the mixed smelting process is: placing raw materials Al, Co, Cr, Fe, Ti, Ta, B and Ni in a smelting furnace in proportion, and smelting them multiple times under electromagnetic stirring.

[0055] In some embodiments, the mixed smelting process specifically includes: placing raw materials Al, Co, Cr, Fe, Ti, Ta, B and Ni in a vacuum arc melting furnace in proportion, and smelting for more than 5 times under electromagnetic stirring conditions.

[0056] In some embodiments, the raw materials Al, Co, Cr, Fe, Ti, Ta, B and Ni have been subjected to mechanical methods to remove surface oxide scales to ensure the purity of the raw materials.

[0057] An embodiment of the present invention also provides an application of the high entropy alloy having both room temperature and high temperature toughness as described in any of the aforementioned embodiments in the fields of aerospace, petrochemical or power equipment.

[0058] The present invention will be further described below by means of specific examples.

[0059] Example 1

[0060] This embodiment provides a high entropy alloy HEA1 having both room temperature and high temperature toughness and a preparation method thereof. The chemical formula of HEA1 is (Ni2CoCr 1.3 Fe)Al5Ti4Ta 1.5 B 0.4 , the chemical composition is shown in Table 1, and the preparation method is as follows:

[0061] Prepare the raw materials Al, Co, Cr, Fe, Ti, Ta, B and Ni according to the chemical composition shown in Table 1, and remove the surface oxide scale of the raw materials by mechanical methods; place the treated raw materials in a vacuum arc melting furnace, and melt them more than 5 times under the condition of electromagnetic stirring. Each time the alloy is melted, the titanium ingot is first melted for deoxidation, which lasts for 1 minute, and the alloy ingot is turned over to make the composition uniform. During the melting, the electromagnetic stirring is turned on for full stirring, and each melting time lasts for 1 minute. After the melting is completed, cast into alloy ingots, cool to room temperature and take samples.

[0062] The obtained alloy ingot is homogenized at 1150°C for 2 hours and cooled to room temperature; the homogenized alloy ingot is rolled at a reduction of 5 to 10% each time to obtain a plate with a total reduction of 70%; the obtained plate is recrystallized at 1150°C for 5 minutes and cooled to room temperature; the recrystallized plate is subjected to two-step aging treatment, firstly at 1000°C for the first step aging treatment, at a heat preservation time of 20 minutes, and cooled to room temperature; and then at 800°C for the second step aging treatment, at a heat preservation time of 2 hours, and cooled to room temperature, to finally obtain a high entropy alloy with both room temperature and high temperature strength and toughness.

[0063] Example 2

[0064] This embodiment provides a high entropy alloy HEA2 with both room temperature and high temperature toughness and a preparation method thereof. The chemical formula of HEA2 is (Ni2CoCr 1.4 Fe)Al4Ti4Ta2B 0.1 The chemical composition is shown in Table 1. The preparation method is the same as that in Example 1, except that the chemical composition of the raw materials is adjusted.

[0065] Example 3

[0066] This embodiment provides a high entropy alloy HEA3 having both room temperature and high temperature toughness and a preparation method thereof. The chemical formula of HEA3 is (Ni 1.7 CoCr 1.2 Fe)Al4Ti5Ta 1.5 B 0.4 The chemical composition is shown in Table 1. The preparation method is the same as that in Example 1, except that the chemical composition of the raw materials is adjusted.

[0067] Example 4

[0068] This embodiment provides a high entropy alloy HEA4 with both room temperature and high temperature toughness and a preparation method thereof. The chemical formula of HEA4 is (Ni2CoCr 1.2 Fe)Al4Ti6TaB 0.2 The chemical composition is shown in Table 1. The preparation method is the same as that in Example 1, except that the chemical composition of the raw materials is adjusted.

[0069] Example 5

[0070] This embodiment provides a high entropy alloy HEA5 having both room temperature and high temperature toughness and a preparation method thereof. The chemical formula of HEA5 is (Ni2CoCr 1.3 Fe)Al6Ti4Ta2B 0.2The chemical composition is shown in Table 1. The preparation method is the same as that in Example 1, except that the chemical composition of the raw materials is adjusted.

[0071] Example 6

[0072] The present embodiment provides a high entropy alloy HEA6 having both room temperature and high temperature toughness and a preparation method thereof. The chemical formula and chemical composition of HEA6 are the same as those in Example 1, and the preparation method is the same as that in Example 1, the only difference is that the holding time in the homogenization treatment step is adjusted to 1 hour; the temperature in the recrystallization treatment step is adjusted to 1200°C, and the holding time is adjusted to 2 minutes; the temperature in the first aging treatment step is adjusted to 1050°C, and the holding time is adjusted to 10 minutes; the temperature in the second aging treatment step is adjusted to 850°C, and the holding time is adjusted to 1 hour.

[0073] Example 7

[0074] The present embodiment provides a high entropy alloy HEA7 having both room temperature and high temperature toughness and a preparation method thereof. The chemical formula and chemical composition of HEA7 are the same as those in Example 1, and the preparation method is the same as that in Example 1, the only difference being that the holding time in the homogenization treatment step is adjusted to 1 hour; the temperature in the recrystallization treatment step is adjusted to 1180°C, and the holding time is adjusted to 3 minutes; the temperature in the first aging treatment step is adjusted to 980°C, and the holding time is adjusted to 30 minutes; the temperature in the second aging treatment step is adjusted to 780°C, and the holding time is adjusted to 24 hours.

[0075] Comparative Example 1

[0076] This comparative example provides a high entropy alloy CHEA1 and a preparation method thereof. The chemical formula and chemical composition of CHEA1 are the same as those of Example 1, and the preparation method is the same as that of Example 1, except that the first aging treatment step is omitted.

[0077] Comparative Example 2

[0078] This comparative example provides a high entropy alloy CHEA2 and a preparation method thereof. The chemical formula and chemical composition of CHEA2 are the same as those of Example 1, and the preparation method is the same as that of Example 1, except that the second aging treatment step is omitted.

[0079] Comparative Example 3

[0080] This comparative example provides a high entropy alloy CHEA3 and a preparation method thereof. The chemical formula of CHEA3 is (Ni2CoCrFe)Al5Ti5TaB 0.1 The chemical composition is shown in Table 1. The preparation method is the same as that in Example 1, except that the chemical composition of the raw materials is adjusted.

[0081] Comparative Example 4

[0082] This comparative example provides a high entropy alloy CHEA4 and a preparation method thereof. The chemical formula of CHEA4 is (NiCoCrFe)Al3Ti3TaB 0.1 The chemical composition is shown in Table 1. The preparation method is the same as that in Example 1, except that the chemical composition of the raw materials is adjusted.

[0083] Table 1 shows the chemical compositions (atomic percentage at. %) of HEA1 to HEA7 in Examples 1 to 7 and CHEA1 to CHEA4 in Comparative Examples 1 to 4.

[0084] Table 1

[0085]

[0086]

[0087] Figure 1 It is the equilibrium phase diagram of the high entropy alloy in Example 1 calculated according to the Thermal-calc software, showing the change of different phases with temperature. According to the figure, the L12 phase in the high entropy alloy begins to dissolve at 1100°C, and the σ phase begins to dissolve at 950°C. Therefore, the alloy after recrystallization treatment is subjected to the first step of high temperature aging treatment at 980-1050°C, which is conducive to the formation of part of the primary L12 phase at the grain boundary, and then the second step of low temperature aging treatment is carried out at 780-850°C to promote the formation of the secondary L12 phase and increase the volume fraction of the L12 phase. During the high temperature aging process, the primary L12 precipitated phase is preferentially precipitated at the grain boundary, occupying the grain boundary nucleation site, thereby reducing the grain boundary energy, effectively inhibiting the formation of the σ phase during the low temperature aging process, and avoiding the occurrence of medium temperature brittleness of the high entropy alloy. This shows that the two-step aging treatment step in the preparation method provided by the present invention is well-founded and very critical.

[0088] Figure 2 is a scanning electron microscope image of the alloy structure of the high entropy alloy in Example 1, Figure 3 is a scanning electron microscope image of the alloy structure of the high entropy alloy in Example 1, Figure 4 is a scanning electron microscope image of the alloy structure of the high entropy alloy in Example 2. Figure 2 to Figure 4It can be seen that in Example 1, after two-step aging treatment, there is a high-density L12 nano-precipitate phase with a bimodal distribution (first size and second size) in the FCC matrix, with an average radius of about 50nm and 10nm, respectively, and no other harmful phases are found at the grain boundaries. However, in Comparative Example 1, only the second-step aging treatment is performed, and in addition to the formation of an L12 nano-precipitate phase of about 30nm in its FCC matrix, a large amount of σ phase is formed at the grain boundaries, indicating that the two-step aging treatment in the present invention can significantly inhibit the formation of σ phase. In Comparative Example 2, which is only subjected to the first-step aging treatment, although no other harmful phases are observed at the grain boundaries, the volume fraction of the L12 nano-precipitate phase is less than that of the precipitate phase in Example 1, and its strengthening effect is limited. Therefore, the present invention can not only obtain a high volume fraction of L12 nano-precipitates through a reasonable two-step aging treatment process, but also inhibit the formation of σ phases at grain boundaries during the aging process, thereby improving the high-temperature mechanical properties of high-entropy alloys.

[0089] For HEA1-HEA7 prepared in the above Examples 1-7 and CHEA1-CHEA4 prepared in Comparative Examples 1-4, tensile specimens were processed by wire cutting and room temperature tensile tests were carried out on an MTS testing machine. The yield strength, tensile strength and elongation after fracture of HEA1-HEA7 and CHEA1-CHEA4 are shown in Table 2; tensile specimens were processed by wire cutting and 800°C high temperature tensile tests were carried out on an MTS testing machine. The yield strength, tensile strength and elongation after fracture of HEA1-HEA7 and CHEA1-CHEA4 are shown in Table 3.

[0090] Table 2

[0091]

[0092]

[0093] Table 3

[0094] High Entropy Alloy Number Yield strength(MPa) Tensile strength(MPa) Elongation(%) HEA1 942 1045 12 HEA2 998 1077 8 HEA3 983 1069 10 HEA4 991 1070 9 HEA5 945 1053 11 HEA6 944 1051 11 HEA7 920 1045 10 CHEA1 1021 1097 2 CHEA2 757 832 12 CHEA3 730 812 0.5 CHEA4 722 775 10

[0095] According to the data in Table 2, it can be seen that the yield strength of the high entropy alloys prepared in Examples 1 to 7 at room temperature is greater than or equal to 1100MPa, the tensile strength is greater than or equal to 1500MPa, and the elongation is greater than or equal to 15%, indicating that the high entropy alloy of the present invention has excellent strength-plasticity matching at room temperature. In addition, relative to Example 1, Comparative Example 1 omits the first aging treatment step, and the tensile strength and elongation of the alloy prepared therefrom at room temperature are greatly reduced, and Comparative Example 2 omits the second aging treatment step, and the yield strength and tensile strength of the alloy prepared therefrom at room temperature are greatly reduced, indicating that the high entropy alloy in Example 1 has better comprehensive mechanical properties at room temperature.

[0096] According to the data in Table 3, it can be seen that the yield strength of the high entropy alloys prepared in Examples 1 to 7 at a high temperature of 800°C is greater than or equal to 900MPa, the tensile strength is greater than or equal to 1000MPa, and the elongation is greater than or equal to 8%, indicating that the high entropy alloy of the present invention also has excellent strength-plasticity matching at high temperatures. In addition, relative to Example 1, Comparative Example 1 omits the first aging treatment step, and the elongation of the alloy prepared therefrom at high temperatures is greatly reduced, and Comparative Example 2 omits the second aging treatment step, and the yield strength and tensile strength of the alloy prepared therefrom at high temperatures are greatly reduced, indicating that the high entropy alloy in Example 1 has better comprehensive mechanical properties at high temperatures.

[0097] In addition, in order to further demonstrate the superiority of the high temperature mechanical properties of the high entropy alloy provided by the present invention, the high entropy alloy prepared in Example 1 and other high entropy alloys strengthened by L12 precipitation phase were subjected to the test. 10 Co 25 Cr8Fe 15 Ni 36 Ti6, commercial nickel-based superalloys Inconel 718 and Inconel 625, cobalt-based superalloys Co-9Al-9W-2Ta-2Mo, eutectic high entropy alloy AlCoCrFeNi 2.1 The yield strength at different temperatures was compared. Figure 5 The high entropy alloy prepared in Example 1, Al 10 Co 25 Cr8Fe 15 Ni 36 Ti6, Co-9Al-9W-2Ta-2Mo, Inconel 718, Inconel 625 and AlCoCrFeNi 2.1 The yield strength and temperature curve of the high entropy alloy prepared in Example 1 of the present invention is as follows: 2.1 5 times, and significantly higher than other reported L12 precipitation-strengthened high entropy alloys Al 10 Co 25 Cr8Fe 15 Ni 36 Ti6 and cobalt-based high-temperature alloy Co-9Al-9W-2Ta-2Mo, as well as commercial nickel-based high-temperature alloys Inconel 718 and Inconel 625. Therefore, the high entropy alloy provided by the present invention has excellent high-temperature mechanical properties.

[0098] In summary, the present invention provides a high entropy alloy with both room temperature and high temperature toughness, and the chemical composition includes, in atomic percentage, 4.0-6.0% Al, 15.0-20.0% Co, 20.0-25.0% Cr, 15.0-20.0% Fe, 4.0-6.0% Ti, 0.5-2.0% Ta, 0.1-0.5% B, and the rest is Ni; and 10.0%≤(Ti+Al+Ta)≤12.0%, (Cr+Fe)≤40.0%. The high entropy alloy with both room temperature and high temperature toughness provided by the present invention exhibits good room temperature and high temperature mechanical properties, with a yield strength of greater than or equal to 1100MPa, a tensile strength of greater than or equal to 1500MPa, and an elongation of greater than or equal to 15% at room temperature; the yield strength at a temperature of 800°C is greater than or equal to 900MPa, the tensile strength is greater than or equal to 1000MPa, and the elongation is greater than or equal to 8%, and can be well applied to aerospace, petrochemical, power equipment and other fields.

[0099] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A high entropy alloy having both room temperature and high temperature toughness, characterized in that: The chemical composition of the high entropy alloy includes, in atomic percentage, 4.0-6.0% Al, 15.0-20.0% Co, 20.0-25.0% Cr, 15.0-20.0% Fe, 4.0-6.0% Ti, 0.5-2.0% Ta, 0.1-0.5% B, and the rest Ni; and satisfies 10.0%≤(Ti+Al+Ta)≤12.0%, (Cr+Fe)≤40.0%.

2. The high entropy alloy having both room temperature and high temperature toughness according to claim 1, characterized in that: The chemical composition of the high entropy alloy includes, in atomic percentage, 4.0-6.0% Al, 16.5-18.5% Co, 20.5-23.5% Cr, 16.5-18.5% Fe, 4.0-6.0% Ti, 1.5-2.0% Ta, 0.1-0.4% B, and the rest Ni; and satisfies 10.0%≤(Ti+Al+Ta)≤12.0%, (Cr+Fe)≤40.0%.

3. The high entropy alloy having both room temperature and high temperature toughness according to claim 1, characterized in that: The alloy structure of the high entropy alloy includes an FCC matrix and an L12 nano-precipitated phase.

4. The high entropy alloy having both room temperature and high temperature toughness according to claim 3, characterized in that: In the alloy structure of the high entropy alloy, the volume fraction of the L12 nano-precipitated phase is greater than or equal to 35%.

5. The high entropy alloy having both room temperature and high temperature toughness according to claim 3, characterized in that: The L12 nano-precipitated phase has a first size and a second size, the first size is 40-100 nm, and the second size is 1-20 nm.

6. The high entropy alloy having both room temperature and high temperature toughness according to claim 1, characterized in that: At room temperature, the yield strength of the high entropy alloy is greater than or equal to 1100 MPa, the tensile strength is greater than or equal to 1500 MPa, and the elongation is greater than or equal to 15%; at a temperature of 800°C, the yield strength of the high entropy alloy is greater than or equal to 900 MPa, the tensile strength is greater than or equal to 1000 MPa, and the elongation is greater than or equal to 8%.

7. A method for preparing a high entropy alloy having both room temperature and high temperature toughness as claimed in any one of claims 1 to 6, characterized in that: Includes steps: The raw materials Al, Co, Cr, Fe, Ti, Ta, B and Ni are mixed and smelted in proportion, cast into alloy ingots after smelting, and cooled to room temperature; The obtained alloy ingot is homogenized at 1100-1200°C for 1-2 hours and then cooled to room temperature; The alloy ingot which has been homogenized is rolled at a reduction of 5 to 10% each time to obtain a plate with a total reduction of 60 to 80%; The obtained plate is subjected to recrystallization treatment at 1150-1200°C for 2-5 minutes and then cooled to room temperature; The recrystallized plate is subjected to a two-step aging treatment. The first step of aging treatment is carried out at 980-1050°C for 10-30 minutes, and then cooled to room temperature. The second step of aging treatment is continued at 780-850°C for 1-24 hours, and then cooled to room temperature to obtain a high-entropy alloy with both room temperature and high temperature strength and toughness.

8. The method for preparing a high entropy alloy having both room temperature and high temperature toughness according to claim 7, characterized in that: The purity of the raw materials Al, Co, Cr, Fe, Ti, Ta, B and Ni is greater than or equal to 99.95%.

9. The method for preparing a high entropy alloy having both room temperature and high temperature toughness according to claim 7, characterized in that: The mixed smelting process is as follows: raw materials Al, Co, Cr, Fe, Ti, Ta, B and Ni are placed in a smelting furnace in proportion, and smelted multiple times under electromagnetic stirring.

10. Use of the high entropy alloy having both room temperature and high temperature toughness as claimed in any one of claims 1 to 6 in the fields of aerospace, petrochemical or power equipment.

Citation Information

Patent Citations

  • High-entropy alloy with dispersion nano-sized precipitate strengthening effect and preparing method thereof

    CN104694808A